2010
DOI: 10.1111/j.1464-410x.2010.09938.x
|View full text |Cite
|
Sign up to set email alerts
|

Native nephrectomy for autosomal dominant polycystic kidney disease: before or after kidney transplantation?

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? The indications and timing of native nephrectomy in patients with autosomal dominant polycystic kidney disease (ADPKD) is controversial, especially for those undergoing renal transplantation. Post‐transplant unilateral native nephrectomy appears to be the preferred intervention compared to pre‐transplant native nephrectomy. There seems to be substantial additive risk to bilateral over unilateral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 20 publications
2
50
0
12
Order By: Relevance
“…On the other hand, there are many authors who hold that it is wise to avoid any pre-transplant or simultaneous procedures (17,18). According to the retrospective analysis of these studies' outcomes, the estimated percentage of the patients with in vivo 31: 307-312 (2017) 310 (20) + ADPKD that needed NN was relatively low (around 20%) and the majority of complications that led to NN occurred during the post-transplant period (11,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are many authors who hold that it is wise to avoid any pre-transplant or simultaneous procedures (17,18). According to the retrospective analysis of these studies' outcomes, the estimated percentage of the patients with in vivo 31: 307-312 (2017) 310 (20) + ADPKD that needed NN was relatively low (around 20%) and the majority of complications that led to NN occurred during the post-transplant period (11,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that concomitant unilateral or bilateral nephrectomy and transplantation are feasible and safe [18][19][20][21], while others preferred to perform NN in a pretransplant setting in order to increase the available space for the transplant, reduce the risk of post-transplant graft loses, and obtain a relief of the symptoms [3]. Moreover, Kirkman suggests a post-transplant unilateral nephrectomy due to the significant morbidity after pretransplant native nephrectomy in ADPKD patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Néanmoins, cette voie d'abord requiert une large incision sous-costale ou une lombotomie qui entraînent une morbidité significative : Bennett rapporte un taux de 38 % de complications et une mortalité de 3 % sur une série de 31 patients traités par néphrectomie ouverte [3]. Des publications plus récentes rapportent des taux de complication entre 36 et 40 % [4,5,10,11]. C'est pour diminuer la morbidité que la voie laparoscopique a été décrite dans quelques séries pionnières [4,8].…”
Section: Discussionunclassified